2021
DOI: 10.1097/bsd.0000000000001284
|View full text |Cite
|
Sign up to set email alerts
|

Is There a Correlation Between Cobb Angle and Pulmonary Function Tests at 2-year Follow-up in Patients With Severe Spinal Deformity Treated by Posterior Vertebral Column Resection?

Abstract: Study design: A retrospective study. Objective: The aim was to evaluate the relationships of Cobb angle and pulmonary function tests (PFTs) changes in severe spinal deformity and underwent posterior vertebral column resection (PVCR). Summary of Background Data: No previous study focused on the correlation of deformity correction and PFTs changes in patients with cobb angle >90 degrees. Methods: PFTs values [forced vita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
3
2

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 32 publications
0
3
2
Order By: Relevance
“…By contrast, all patients who underwent only low-grade osteotomy rather than 3-column osteotomy in this study had not presented the shortening of thoracic spine. As a result, the mean FVC increased from 1.59 to 1.95 L (increase of 0.36 L) in the study of Zhang et al, 16 which was less than the value of our study (increase of 0.55 L). Inspiringly, for patients with SRSS, it is necessary to maintain the original length of thoracic spine and correct thoracic deformity as much as possible to obtain the greatest improvement in lung function and volume.…”
Section: Discussioncontrasting
confidence: 90%
See 4 more Smart Citations
“…By contrast, all patients who underwent only low-grade osteotomy rather than 3-column osteotomy in this study had not presented the shortening of thoracic spine. As a result, the mean FVC increased from 1.59 to 1.95 L (increase of 0.36 L) in the study of Zhang et al, 16 which was less than the value of our study (increase of 0.55 L). Inspiringly, for patients with SRSS, it is necessary to maintain the original length of thoracic spine and correct thoracic deformity as much as possible to obtain the greatest improvement in lung function and volume.…”
Section: Discussioncontrasting
confidence: 90%
“…The mean FVC, FVC%, FEV1, and TLC increased from 1.67 L, 51.13%, 1.47 L, and 2.37 L to 1.95 L, 64.35%, 1.75 L, and 2.78 L, respectively, after HPT and further improved to 2.22 L, 72.14%, 1.95 L, and 3.15 L, respectively, at the final follow-up. The mean blood loss of 1490.8 mL and mean operation time of 269.8 mins in the patients of our study were significantly less than the values of the reported study by Zhang et al 16 In addition, no serious irreversible neurological complications and deep infection occurred after surgery. Taken together, preoperative HPT combined with posterior multilevel Ponte osteotomy is a more feasible and safer operative strategy compared with 1-stage PVCR surgery.…”
Section: Discussioncontrasting
confidence: 68%
See 3 more Smart Citations